Pengaruh Kesadaran WP, Kualitas Pelayanan, Kewajiban Moral, Sanksi, Pemeriksaan Pada Kepatuhan WP Hotel BAPENDA Badung - Dewi, Putu Arisna; Jati, I Ketut (E-Jurnal Akuntansi; Vol 28 No 2 (2019)DO - 10.24843/EJA.2019.v28.i02.p25, 2019)
The purpose of this study was to determine the effect of taxpayer awareness, service quality, moral obligations, tax sanctions and tax audits of hotel taxpayer compliance in the Regional Revenue Agency of Badung Regency. The number of samples used is 96 hotel taxpayers in the Regional Revenue Agency of Badung Regency. The research instrument used was a questionnaire with data analysis techniques namely multiple linear regression analysis. The sample used was determined by the nonprobability sampling method, namely incidental sampling. Based on the results of this study it was found that variable awareness of taxpayers, service quality, moral obligations, tax sanctions and tax audits had a positive effect on hotel taxpayer compliance in the Regional Revenue Agency of Badung Regency. That is, the better awareness of taxpayers, service quality, moral obligations, tax sanctions and tax audits will encourage hotel taxpayers to fulfill their tax obligations. Keywords : Awareness, service quality, obligations, taxpayer compliance, tax sanctions.